2015
DOI: 10.1002/etc.2880
|View full text |Cite
|
Sign up to set email alerts
|

Application of endocrine disruptor screening program fish short‐term reproduction assay: Reproduction and endocrine function in fathead minnow (Pimephales promelas) and killifish (Fundulus heteroclitus) exposed to Bermuda pond sediment

Abstract: A modified tier 1 Endocrine Disruptor Screening Program (EDSP) 21-d fish short-term reproduction assay (FSTRA) was used to evaluate the effects of sediment exposure from freshwater and brackish ponds in Bermuda on reproductive fecundity and endocrine function in fathead minnow (Pimephales promelas) and killifish (Fundulus heteroclitus). Reproductively active male and female fish were exposed to control sediment and sediment from 2 freshwater ponds (fathead minnow) and 2 marine ponds (killifish) contaminated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Developmental deformities have also been identified in endemic killifish ( Fundulus bermudae ) , mosquitofish ( Gambusia affinis ) , and diamondback terrapins in Bermuda. More recently, Fort et al report reproduction and endocrine dysfunction in surrogate fish, fathead minnow ( Pimephales promelas ) and killifish ( Fundulus heteroclitus ), exposed to freshwater and marine sediment from Bermuda. In an effort to determine the role of metals and PAHs in the sediments from Bermuda on developmental, reproductive, endocrine, and immune processes in developing R. marina , a sediment spiking study was performed (D.J.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental deformities have also been identified in endemic killifish ( Fundulus bermudae ) , mosquitofish ( Gambusia affinis ) , and diamondback terrapins in Bermuda. More recently, Fort et al report reproduction and endocrine dysfunction in surrogate fish, fathead minnow ( Pimephales promelas ) and killifish ( Fundulus heteroclitus ), exposed to freshwater and marine sediment from Bermuda. In an effort to determine the role of metals and PAHs in the sediments from Bermuda on developmental, reproductive, endocrine, and immune processes in developing R. marina , a sediment spiking study was performed (D.J.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadal abnormalities observed in adult toads from several sites suggested that endocrine‐disrupting chemicals may have affected the process of gonad differentiation in these animals . Furthermore, sediments from Cloverdale and Warwick Ponds were shown to impair reproduction and affect steroidogenesis in fathead minnows . Steroidogenesis in larval toads inhabiting the same ponds was similarly affected (D.J.…”
Section: Introductionmentioning
confidence: 99%